A longevidade no aprendizado de línguas: acrescentando vida aos anos e não anos a vida - Villani, Fábio Luiz (2007)
The objective of this study is to investigate de learning and teaching process of people between sixty and eighty years old. During the process we intend to observe the forms of inclusion of these people using the English language as a tool to freedom. As base for these reflections some ideas of educators will be discussed such as: Freire (1980, 1983, 1984, 1987, 1996, 2000 and 2001), Celani (1996, 2000 and 2001) and Pennycook (1994 and 1999) among many others. The used methodology will be phenomenology according to van Manen (1990). We hope with this study to offer an alternative to people to face aging as a normal stage of life where people can study (or come back to) school and also participate actively in modern society. For this, we present in the first part of this study, a description of aging until the current days. In the second part of the the research the focus is directed to an elderly group that studies English in a catholic church of São Paulo city having the researcher as teacher and participant of this group. As conclusion we present a suggestion of a political pedagogical project construction for third age courses where the inclusion and freedom must be the main contemplated aspects